(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2024)
One of the technical issues arising from deregulation is transmission line congestion. The size and location of FACTS controllers like thyristor-controlled series compensators (TCSCs) and static VAR compensator (SVC) devices significantly affect their efficiency in congestion management problems. As a nonlinear problem, locating and sizing these devices in a power network is difficult. To solve this issue, this paper presents the technique for optimal FACTS placement using the giant trevally optimizer (GTO) algorithm for congestion management (CM). Three objective functions are considered to reduce the congestion, including voltage stability and eliminating real power loss overall cost. To determine the best location for FACTS devices in the MATLAB R2020b tool, the suggested GTO approach is implemented and discussed for the IEEE 14-bus and IEEE 30-bus systems. It is also compared with existing GSA, BBO, and ICSA approaches under three loading situations. From the simulation results, GTO minimized total costs and real power losses better than existing algorithm algorithms, and GTO provides high net saving costs.